Propagation dynamics of vector vortex beams in a strongly nonlocal nonlinear medium with parity-time-symmetric potentials. (4th February 2022) - Yao, Gang; Chew, Khian-Hooi; Wu, Yan; Li, Yuhua; Chen, Rui-Pin
Abstract: We demonstrate the dynamical properties of a vector vortex optical field (VVOF) in a strongly nonlocal nonlinear medium (SNNM) with sine and cosine parity-time-symmetric potentials (SCPT) by using the coupled vector Snyder-Mitchell model. Our study shows that the shape of the optical field is chaotically distorted in different propagation distances due to the modulation of complex refractive index. Despite the distorted optical field, the VVOF reciprocally evolves in a periodic stretch and shrink behavior during propagation in the SNNM-SCPT. The reciprocal conversions between the linear and circular polarizations periodically occur during propagation. The evolution of VVOF and the linear and circular polarization conversions are strongly dependent on the modulation of the complex refractive index, the initial powers and the vortex topological charge numbers. These results can provide a new way to complexly manipulate the VVOF in a SNNM-SCPT.